The potential role of Ku80 in primary central nervous system lymphoma as a prognostic factor - Li, Xinwei; He, Xinjia; Xu, Xueying; Song, Zhengfei; Qian, Chong; Wang, Jin; Wang, Yirong (Contemporary Oncology/Współczesna Onkologia, 2013)
The aim of our study was to detect the expression of Ku80 in primary central nervous system lymphoma and to evaluate the relationship between Ku80 expression level and clinical outcomes. Thirty-eight patients with primary central nervous system lymphoma (PCNSL) were included in this retrospective study. The expression of Ku80 in tumor samples was determined by immunohistochemistry. One thousand neoplastic cells per specimen were counted. The expression levels were compared with the clinical data and statistically analyzed. The results of this study show that the expression of Ku80 can be found in the majority of PCNSLs. The mean expression level of Ku80 in 38 PCNSL is 64.1 ±24.5. A significant difference in Ku80 expression could be found between the age < 65 years group and age  65 years group (P = 0.006). Kaplan-Meier analysis revealed that patients who showed a high Ku80 expression had a significantly shorter median survival time (MST) than patients who had low Ku80 expression (P = 0.036). Patients’ age, tumor location, and treatment protocol were significantly related to prognosis in PCNSL (P < 0.05). The expression of Ku80 was observed in the majority of PCNSLs. Ku80 was a predictive factor for survival in this study. In addition to Ku80, other clinical variables including age, tumor location and therapeutic protocol are correlated significantly with overall survival.